The ENGLISH FOREIGN LANGUAGE (EFL) TEACHERS' STRATEGIES APPLIED IN MANAGING ENGLISH CLASS - St Zumarotum Mas'ulah; Moh. Zainuddin; iin Widya Lestari; St Zumarotum Mas'ulah; Moh. Zainuddin; iin Widya Lestari (INTENS (International Journal of English Education and Linguistics), 2025)
Managing an English class is a complex task for teacher. In this abstract, the researcher will explore various strategies used by teachers to manage English classes effectively. Teachers must pay attention to various factors, including the level of students’ language skills, various factors, including the level of students' language skills, various learning styles, and challenges that arise in teaching foreign languages. One of the main strategies is the use of a variety of teaching methods, such as project-based learning, language games. In this way, teachers can make learning more interesting and relevant for students. Apart from that, teachers must also have good classroom management skills. This includes the ability to create a positive and inclusive environment, manage time efficiently, and deal effectively with student behaviour. The researcher used qualitative method, and two participant/ two teachers to be interview. And also the researcher used instruments and interview, and the school at MTs Al- Yakin Pungpungan.